The Implementation of British Parliamentary Debating in Mulawarman Debate Society (MDS) - Lely Agustina; Bahrani Bahrani (Indonesian Journal of EFL and Linguistics, 2016)
In English debate, the students will be exposed to the real problems facing a society or a nation.  The students are required to be able to give a strong and reasonable statement and solution so that they can practice English and convince the public that their idea will be expressed freely. This study found that there were some differences related to the implementation of British Parliamentary debating system, such us the differences of the amount of debater and adjudicator and length of speech. Those differences actually did not give bad effect significantly during the observation because of during observations, each member acted his or her role as well as the regulation of British Parliamentary debating system. It can be said that they had fulfilled their role fulfillment as debater, time keeper or the speaker and as adjudicator in every single debating practice. Beside the differences mentioned above, everything related to the implementation of British Parliamentary debating system in Mulawarman Debating Society were the same as the standard regulation of the British Parliamentary Debating System. For instance, there was case building for fifteen minutes before debating, the debater delivered POI, both accepted and declined it, and in the debate practice of MDS, the adjudication was also done by the adjudicator through giving verbal adjudication and ranking the team. The motion was also given by the adjudicator in the debate practice of MDS.